Common inherited loss-of-function mutations in the innate sensor NOD2 contribute to exceptional immune response to cancer immunotherapy - Megan B. Barnet; Katherine J. L. Jackson; Etienne Masle-Farquhar; Amanda Russell; Deborah L. Burnett; Adrian Chye; Chris J. Jara; Megan Faulks; Amanda Mawson; Timothy J. Peters; Robert Brink; Katherine Wright; et al. (Proceedings of the National Academy of Sciences, 2025)
Lung cancers and melanomas have many somatically mutated self-proteins that would be expected to trigger an immune rejection response, yet therapeutic responses can only be induced in a subset of patients. Here, we investigated the possibility that inherited differences in immune tolerance checkpoints contribute to variability in outcomes. Whole genome sequencing revealed biallelic germline loss-of-function (LOF) mutations in the immune tolerance checkpoint gene, NOD2 , in an exceptional immune responder to targeted radiotherapy for metastatic melanoma. In 40 exceptional immune responders to anti-PD1 monotherapy for non–small cell lung cancer (NSCLC), genome sequencing showed 30% had inherited a NOD2 LOF variant, more than twice the population frequency ( P = 0.0021). Conversely, a gain-of-function RIPK2 allele known to increase NOD2 signaling was inherited by 61% of nonresponders from the same cohort, compared to 10% of exceptional responders and much higher than the population frequency ( P < 0.0001). Within the overall recruited cohort of 144 NSCLC anti-PD1 patients, individuals with immune-related adverse events (irAE) had better overall survival, further improved in those with NOD2 LOF. In independent anti-PD1 monotherapy cohorts with a range of cancers, inherited NOD2 LOF was associated with complete or partial response ( P = 0.0107). Experimental validation in mice showed germline Nod2 LOF enhanced therapeutic immune responses elicited by anti-PD1 monotherapy against a high mutation burden colorectal cancer, increasing tumor infiltration by effector memory CD8 T cells. Collectively these results reveal common inherited human variation in an immune tolerance checkpoint is a determinant of cancer immune responses elicited by pharmacological inhibition of another checkpoint.